MM Azami’s Contribution to Countering Hadith Skepticism and Its Influence in Indonesia - Rahman, Andi; Hakim, Lukman; Khoirul Anwar, Muhammad (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
Western scholars’ objections to the authenticity of hadiths began from the 19th century until the 20th century. They argued with various skeptical narratives that the hadith of the Prophet Muhammad never existed. In the dynamics of hadith studies, the ideas of Western scholars have become a new paradigm that has sparked serious responses from Muslim scholars including Mustafa Azami. This article aims to analyze Azami’s role in fighting Western Scholars’ Hadith skepticism, as well as Azami’s influence in Indonesia as a pioneer of this study. This article uses a qualitative method involving literature review, and then analyzes it using Thomas Khuns’ paradigm shift theory. This article concludes that Azami has proven the Hadith Skepticism thesis put forward by Western scholars, which is not sustainable because there is inequality in the realm of hadith science. Likewise, Western scholars’ ideas about the authenticity of hadith have also not been developed. Meanwhile, Azami's academic work has had a huge impact on hadith studies in Indonesia.